Semi-Solid Processing of Aluminum Alloys - Nafisi, Shahrooz; Ghomashchi, Reza (Springer International Publishing : Imprint: Springer, 2016)
This book describes in great detail the semi-solid processing of aluminum alloys. The authors examine the fundamentals of semi-solid metal processing, provide guidelines for research, illustrate the tools that are employed, and explain the measured parameters for semi-solid processing characterization.